The role of soil flux and soil gas monitoring in the characterisation of a CO2 surface leak: A case study in Qinghai, China. (November 2016) - Schroder, I.F.; Zhang, H.; Zhang, C.; Feitz, A.J.
Highlights: The sample design of soil flux surveys must be fit for purpose. An irregular sampling grid is ideal for quantification of surface emissions. Ratios of soil gases from portable measurements can be used to infer CO2 source. Subsurface gas migration limits usefulness of point measurements for leak detection. Abstract: Following the drilling of a shallow natural CO2 reservoir at the Qinghai research site, west of Haidong, China, it was discovered that CO2 was continuously leaking from the wellbore due to well-failure. The site has become a useful research facility in China for studying CO2 leakage and monitoring technologies for application to geological storage sites of CO2 . During an eight day period in 2014, soil gas and soil flux surveys were conducted to characterise the distribution, magnitude and likely source of the leaking CO2 . Two different sampling patterns were utilised during soil flux surveys. A regular sampling grid was used to spatially map out the two high-flux zones which were located 20–50 m away from the wellhead. An irregular sampling grid, with higher sampling density in the high-flux zones, allowed for more accurate mapping of the leak distribution and estimation of total field emission rate using cubic interpolation. The total CO2 emission rate for the site was estimated at 649-1015 kgCO2 /d and there appeared to be some degree of spatial correlation between observed CO2 fluxes and elevated surface H2 O fluxes. Sixteen soil gas wells were installed across the field to test the real-time application of Romanak et al.'s (2012) process-based approach for soil gas measurements (using ratios of major soil gas components to identify the CO2 source) using a portable multi-gas analyser. Results clearly identified CO2 as being derived from one exogenous source, and are consistent with gas samples collected for laboratory analysis. Carbon-13 isotopes in the centre of each leak zone (−0.21‰ and −0.22‰) indicate the underlying CO2 is likely sourced from the thermal decomposition of marine carbonates. Surface soil mineralisation (predominantly calcite) can be used to infer prior distribution of the CO2 hotspots and as a consequence highlighted plume migration of 20 m in 11 years. The broadening of the affected area beyond the wellbore at the Qinghai research site markedly increases the area that needs surveying at sufficient density to detect a leak. This challenges the role of soil gas and soil flux in a CCS monitoring and verification program for leak detection, suggesting that these techniques may be better applied for characterising the source and emission rate of a CO2 leak, respectively.